2014
DOI: 10.1074/jbc.m114.582882
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Transcriptional Activity Is Modulated by FK506-binding Proteins FKBP51 and FKBP52

Abstract: Background: Hsp90 binding immunophilins may be regulators of the NF-B mechanism of action. Results: FKBP51 and FKBP52 show antagonistic properties on the nuclear accumulation and transcriptional activity of NF-B. Conclusion: Both immunophilins modulate NF-B trafficking and NF-B transcription when they are recruited to the promoter regions of target genes. Significance: The competitive effect between both immunophilins in different cell types may explain the pleiotropic actions of NF-B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(113 citation statements)
references
References 83 publications
3
107
1
Order By: Relevance
“…Thus, it has been shown that Hsp90 and p23 are both recruited to glucocorticoid-responsive elements upon steroid activation of the GR [132]. The need of FKBP51 is in agreement with the effect of this IMM on the nuclear retention of nuclear factors by competition with the anchoring effect of FKBP52 [36,110]. A similar effect is observed in FKBP52 KO cells and due to the overexpression of the TPR peptide, which abolishes the nuclear pool of steroid receptors in the nucleus due to a 'dominant-negative' effect on receptor anchorage to nuclear structures [36].…”
Section: Nuclear Eventssupporting
confidence: 62%
See 2 more Smart Citations
“…Thus, it has been shown that Hsp90 and p23 are both recruited to glucocorticoid-responsive elements upon steroid activation of the GR [132]. The need of FKBP51 is in agreement with the effect of this IMM on the nuclear retention of nuclear factors by competition with the anchoring effect of FKBP52 [36,110]. A similar effect is observed in FKBP52 KO cells and due to the overexpression of the TPR peptide, which abolishes the nuclear pool of steroid receptors in the nucleus due to a 'dominant-negative' effect on receptor anchorage to nuclear structures [36].…”
Section: Nuclear Eventssupporting
confidence: 62%
“…Very recent findings from our laboratory also demonstrated that the NF-B transport towards the nucleus is also regulated by the expression balance of the TPR-domain IMMs FKBP52 and FKBP51 [110]. Interestingly, NF-B is not chaperoned by Hsp90, which assigns a cardinal role to these TPR proteins per se.…”
Section: Nuclear Eventsmentioning
confidence: 78%
See 1 more Smart Citation
“…24 As shown in Supplementary Figure 4, both wt and K422R FKBP51 inhibit NF-κB activity and interact with NF-κB, showing that mutation of K422 does not alter the general function of the protein.…”
Section: Resultsmentioning
confidence: 86%
“…ChIP experiments were performed in CNE-1/2 cells using the ChIP assay kit (Millipore, Billerica, MA, USA) (Erlejman et al 2014). Briefly, proteins and DNA were cross-linked after CNE-1/2 cells were treated with 1 % formaldehyde for 10 min at 37°C and neutralized with glycine added at a final concentration of 0.125 M. Cells were rinsed twice with cold PBS containing 2.5 ml Protease Inhibitor cocktail II (Abcam, Cambridge, MA, USA), scraped, and centrifuged at 72009g for 5 min at 4°C.…”
Section: Chromatin Immunoprecipitation (Chip) Assaysmentioning
confidence: 99%